A systematic literature review to explore lived experiences with phantom limb phenomenon following a lower extremity amputation: a qualitative synthesis - Alabdullah, Abdullah Ali H.; Alyazidi, Saeed Saad; Asiri, Ibrahim Ali; Ali, Hussain Saleh; Almutlaqah, Sarah Abdullah; Alzahrani, Ahmed Saleh; Alzahb, Saeed Abdulrhman; Alasmari, Sumaya Abdullah; Nikolic, Dejan; Radosavljevic, Natasa (Frontiers in Rehabilitation Sciences, 2025)
ObjectiveIn this review we aimed to understand better frequent experiences accompanying phantom limb issues from patients’ perspective and accordingly to generate recommendations for clinical practice.MethodsA systematic literature review approach was utilized and articles meeting the eligibility criteria were critically appraised using the Critical Appraisal Skills Program (CASP). Additionally, a meta-synthesis approach was adopted to combine and analyze the data.ResultsTen relevant studies were critiqued, key themes were: 1) early Information Provision about phantom Limb Pain (PLP) and Participants’ Satisfaction; 2) the PLP's described characteristics; 3) different Emotions and Psychosocial Issues with PLP; 4) the Impact of the PLP on Performing Daily Activities; and 5) the experienced strategies to address the PLP.ConclusionThe experience of phantom limb varies among individuals with lower limb amputation (LLA); however, for many, PLP significantly affects both physical and psychological well-being, adding an additional burden to the overall experience of amputation. Addressing these challenges should begin with early education, followed by a rehabilitation process that considers individual differences in coping mechanisms. Moreover, patients’ preferences should be prioritized when selecting prosthetic devices and determining the most appropriate treatment strategies for managing PLP.